2022
DOI: 10.3389/fncel.2022.953640
|View full text |Cite
|
Sign up to set email alerts
|

Exercise Intervention Modulates Synaptic Plasticity by Inhibiting Excessive Microglial Activation via Exosomes

Abstract: BackgroundExosomes can activate microglia to modulate neural activity and synaptic plasticity by phagocytosis of neural spines or synapses. Our previous research found that an early 4-week exercise intervention in middle cerebral artery occlusion (MCAO) rats can promote the release of exosomes and protect the brain. This study intended to further explore the intrinsic mechanism of neuroprotection by exosome release after exercise.MethodsRats were randomly divided into four groups: the sham operation (SHAM), mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 62 publications
0
13
0
Order By: Relevance
“…Middle cerebral artery occlusion (MCAO) damages the structure and function of synapses, resulting in neurological dysfunction. Serum exosomes from the treatment group effectively inhibited microglia activation, increased the number of synapses and the expression of plasticity‐related proteins, reduced infarct volume, and improved neural function 276,277 . Thus, exosomes can provide a new therapeutic strategy for neuroprotection and repair after stroke.…”
Section: Exosomes In Neuropsychiatric Disordersmentioning
confidence: 98%
See 1 more Smart Citation
“…Middle cerebral artery occlusion (MCAO) damages the structure and function of synapses, resulting in neurological dysfunction. Serum exosomes from the treatment group effectively inhibited microglia activation, increased the number of synapses and the expression of plasticity‐related proteins, reduced infarct volume, and improved neural function 276,277 . Thus, exosomes can provide a new therapeutic strategy for neuroprotection and repair after stroke.…”
Section: Exosomes In Neuropsychiatric Disordersmentioning
confidence: 98%
“…Serum exosomes from the treatment group effectively inhibited microglia activation, increased the number of synapses and the expression of plasticity‐related proteins, reduced infarct volume, and improved neural function. 276 , 277 Thus, exosomes can provide a new therapeutic strategy for neuroprotection and repair after stroke. miR‐190b in ADEs inhibited apoptosis and increased neuronal survival under ischemic conditions.…”
Section: Exosomes In Neuropsychiatric Disordersmentioning
confidence: 99%
“…showed that exercise promotes the expression of synaptic plasticity‐related proteins by regulating exosomal content, which increases the number of synapses in the rat brain and thus promotes the recovery of motor function in an MCAO rat model. Moreover, subsequent experiments by Li et al 136 . demonstrated that exercise intervention regulates synaptic plasticity via inhibition of overactivated microglia via exosomes.…”
Section: Rehabilitation Therapy To Improve Synaptic Dysfunctionmentioning
confidence: 99%
“…135 showed that exercise promotes the expression of synaptic plasticity-related proteins by regulating exosomal content, which increases the number of synapses in the rat brain and thus promotes the recovery of motor function in an MCAO rat model. Moreover, subsequent experiments by Li et al136 demonstrated that exercise intervention regulates synaptic plasticity via inhibition of overactivated microglia via exosomes. Chen et al137 showed that, in an MCAO mouse model, exercise promotes synaptic proliferation and ultimately leads to nerve regeneration by converting astrocytes into neuroprotective reactive astrocytes.…”
mentioning
confidence: 99%
“…Exercise may also regulate synaptic plasticity by promoting the migration of exosomes into the brain [ 272 ] through circulation and by preventing the overactivation of microglia [ 273 ]. Exosomes have been shown to inhibit the overactivation of M1-type microglia [ 274 , 275 ], increase the complexity of dendrites and expression of synaptic plasticity-associated proteins, and significantly reduce the volume of cerebral infarction and dysfunction.…”
Section: Therapeutic Intervention Targeting Microglia In Stroke Rehab...mentioning
confidence: 99%